2022
DOI: 10.3390/life12020297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Efficacy and Safety between 70–150 µm and 100–300 µm Doxorubicin Drug-Eluting Bead Transarterial Chemoembolization for Hepatocellular Carcinoma

Abstract: Background: This study aimed to compare the efficacy and safety of 70–150 μm doxorubicin drug-eluting bead (DEB) transarterial chemoembolization (TACE) with those of 100–300 μm DEB-TACE as first-line treatment in patients with hepatocellular carcinoma (HCC). Methods: We retrospectively investigated 72 patients who underwent TACE with 70–150 μm DEBs (n = 40) or 100–300 μm DEBs (n = 32) for HCC in a tertiary center between March 2013 and May 2019. Initial treatment response and adverse events were assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Several studies reported good outcome in terms of tumor response, PFS, and OS for DEBs <100 μm [ 37 , 38 , 39 ] and >100 μm [ 19 ] in individual single-arm prospective and retrospective studies in HCC patients. While a recent retrospective comparison of DEB-TACE with 70–150 μm DEBs or 100–300 μm DEBs in HCC patients reported no significant differences in tumor response or AEs [ 40 ], prior comparative studies demonstrated favorable efficacy in terms of tumor response and similar or improved OS and PFS after smaller-caliber DEB-TACE compared to medium- or large-size DEBs in HCC patients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported good outcome in terms of tumor response, PFS, and OS for DEBs <100 μm [ 37 , 38 , 39 ] and >100 μm [ 19 ] in individual single-arm prospective and retrospective studies in HCC patients. While a recent retrospective comparison of DEB-TACE with 70–150 μm DEBs or 100–300 μm DEBs in HCC patients reported no significant differences in tumor response or AEs [ 40 ], prior comparative studies demonstrated favorable efficacy in terms of tumor response and similar or improved OS and PFS after smaller-caliber DEB-TACE compared to medium- or large-size DEBs in HCC patients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed procedure for TACE at our institution has been described previously [ 18 , 19 ]. RT was performed for either curative or palliative aims according to the guidelines of the Korean Liver Cancer Association [ 20 , 21 ] and applied after the general condition recovery of patients with a stabilized liver enzyme found in blood chemistry evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…DEE microparticles increase drug concentrations in tumors and reduce systemic drug exposure compared to conventional drug delivery methods. This strategy has proven particularly suitable for transarterial chemoembolization of hepatic malignancies [ 13 , 14 , 15 , 16 ]. Currently, there are seven commercial products for TACE with DEE microparticles [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%